Pengaruh Kompensasi Terhadap Kinerja Karyawan Dengan Motivasi Sebagai Variabel Intervening - Wijaya, Oei, Francis Elizabeth; Zaroni, Zaroni (Ultimaccounting Jurnal Ilmu Akuntansi, 2012)
The objective of this research is to examine the effect of compensation towards employee's performance with motivation as the intervening variable. The data of this research consisted of primary data that was collected by distributing questionnaires to 100 employees in several banks and investment companies in Semarang for the year 2012. The sample in this study determined based on convenience sampling method. The regression analysis and path analysis are used in this study. Based on the analysis data, the result of this study are (1) compensation has a positive influence toward employee performance, (2) compensation has a positive influence toward motivation, (3) motivation has a positive influence toward employee performance, (4) compensation has a positive influence toward employee performance with motivation as the intervening variable. Keywords: compensation, motivation, employee performance, intervening variable.